(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This article highlights the crucial role grammar plays in learning and mastering the English language. It discusses how grammar enhances communication, improves speaking and writing skills, and helps language learners sound more fluent and professional. The article emphasizes that regular practice through reading, listening, and speaking is essential for improving grammar. It also explores how grammar affects career prospects and supports better understanding in multilingual contexts.